(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Burnout Syndrome (BOS) is a psychophysiological syndrome consisting of a triad of emotional and physical exhaustion, an exhibition of an impersonal attitude, and loss of a sense of achievement for oneself. Whereas Professional Quality of Life is the individual’s subjective perception of their position in life. When considering the clinical physical therapist’s nature of job, we find that there is extreme physical exhaustion along with the mental stress in regards to the lesser opportunities they get to pursue their careers ahead. Of all these facts, burnout Syndrome seems quite prevalent among Physiotherapists, though there is sparse data on its prevalence among Physiotherapists and its association with quality of life. There are multiple studies indicating burnout syndrome among doctors, nurses, other para-medical staff along with teachers too, but there is a scarcity of data in terms of Physical therapists. Objectives: This study aimed to find the prevalence of Burnout Syndrome and its association among Clinical physical therapists of government and private hospitals and clinics in Islamabad. Methodology: This descriptive cross-sectional study was conducted from February 2023 to July 2023 through non-probability convenience sampling data was collected from 152 clinical Physical Therapists of private and government hospitals/Clinics in Islamabad. Slovin’s Formula was used to calculate sample size. Data were collected by using self-administered questionnaires consisting of basic socio-demographic information. The Maslach Burnout Inventory (MBI) was used to measure Burnout Syndrome prevalence and to assess the association between burnout and professional quality of life; the Professional Quality of Life Scale (ProQOL) was used. Results: The study showed that 40.2% of participants had burnout syndrome out of 87 participants included in the study. Of the remaining participants (59.8%), 46.2% had low emotional exhaustion, 46.2% had High Depersonalization, and 28.8% had high loss of personal achievements. ProQOL scale showed 72.4% average CS, 73.6% BO, and 60.9% STS. Depersonalization was significantly associated with ProQOL burnout, while other categories of MBI showed insignificant associations. Conclusion: The study concluded that Burnout Syndrome is prevalent among clinical Physical therapists of government and private hospitals/clinics, but there is only a significant association of depersonalization with ProQOL burnout.